Single-leg stability test for knee joint in alpine skiers - Mejovsek, M.; Kasovic, M.; Cigrovski, V.; Loncar, V. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Alpine skiing is a specific activity which demands of a skier good preparedness as well as developed numerous specific abilities. In alpine skiing, and this particularly pertains to the competitive skiing, knee joint is probably the most used joint that also suffers the greatest work-loads, which also makes it the most prone to injuries. The aim of this paper is to investigate the biomechanics of the knee joint which could point towards the existence of injury, therefore reducing the competitive efficiency in alpine skiing.